THE SOCIAL THEORY OF MAX WEBER IN CONFLICT OF INTERPRETATIONS - Zenonas Norkus (Problemos)
The article proposes the survey of the attempts to reconstruct the theoretical core in Weber’s sociological work notorious for its ambiguity in this respect. The work on reconstruction of this core reflects as in the mirror the major shifts in the agenda of contemporary sociology. The confrontation of the system functionalism and conflict sociology during the first post-war decades led to "translation wars" in USA and gave rise to two competing images of Weber - a theorist of social order painted by T. Parsons and as "bourgeois Marx" defended by H. Gerth, C. W. Mills, R. Collins. The renascence of sociological evolutionism in the 1960’s made central the question about the status of Weber’s work on Western rationalism and rationalisation. The two extreme opposing standpoints in this discussion were represented by the vision of Weber as historist (R. Bendix, G. Roth) and as multilinear culturalist evolutionist (F. H. Tenbruck) while W. Schluchter tried to mediate in this conflict seeing Weber’s work as led by "minimalist" evolutionist research program. In all interpretations abovementioned Weber is conceived as a macrosociological theorist whose substantive work stands in tension with his methodological and programmatic texts containing the concept of interpretative sociology, the outline of action theory and avocacy of the methodological individualism. Because of this part of his work Weber was identified (mainly by efforts of A. Schütz) as a progenitor of interpretative sociology too. Coming to prominence in the 1960’s and 1970’s interpretative sociology shifted the focus of theoretical discussion in social theory to the relations between the structure and agency and those between the micro and macro dimensions in social reality. However it was not capable to solve theoretical problems related to those topics. As a new promising theoretical framework for the solution of these problems rational choice approach confronts too the task to come to terms with the work of Max Weber because the history of interpretations of his work teaches us one important lesson: The capability to account for his work providing its assessment and rational reconstruction (if possible in its totality) is an important test of viability for each new approach aspiring for dominance in social theory.